Successful Therapeutic Management of Paralytic Ileus by Using Azithromycin as Motility Modifier in a Cow - S. Sivaraman; Atmakur Venkatesh; A. Kokila; K. Mohanambal; K.K. Ponnu Swamy; D.Sumathi; R. Ravi; S.Dharmaceelan (The Indian Veterinary Journal, 2024)
A primiparous Jersey crossbred cow was presented to large animal medicine unit with the history of anorexia and not voiding dung for past two days. Clinical examination normal vital sign parameters, doughy rumen, absence of rumination and rumen motility, rectal examination showed empty rectum. Auscultation of right paralumbar fossa evidenced irregular pink sound. Abdominocentesis was negative for peritonitis, radiography confirmed the absence of radio opaque foreign body. Ultrasonographic examination was done by using 3.5 to 5.0 MHz sector transducer, examined upper and lower quadrant of right paralumbar fossa, showed distended intestinal loops (4.86±0.84) with hypermotility with in the segment. Hematobiochemical examination showed normal haematological parameters, along with hypoproteinaemia (5.8 g/dL), hypoalbuminemia (1.9 g/dL) and hypokalaemia (2.1 mEq/L). Animal was treated with Azithromycin (1 mg/kg, IV) along with supportive therapy. Animal showed uneventful recovery in 3 days.